Pengaruh Partisipasi Penyusunan Pajak Penghasilan Badan Yang Terutang Terhadap Kinerja Bagian PPh Badan Dengan Koreksi Fiskal Sebagai Penentu Kebijakan - Bayu Adi; Moh Afrizal Miradji (ITB AAS INDONESIA, 2020)
According to Hidayat (2013) in terms of financial statements, there are many contradictions within the company and the many interests that exist within the company in preparing financial statements to prepare their taxes to be compiled as Corporate Tax Income Tax reports (Article 25 Income Tax) many conflicts in preparing corporate tax reports, starting from income tax article 21 to income tax article 25 of the profit / loss statement, so that the tax return can be reported as a corporate taxpayer, then in this case before reporting and avoiding tax errors, a fiscal correction is needed to carry out tax preparation. According to Agustina (2007) states that in the preparation of taxes it is necessary to have coordination from various parties who use interests in the use of company finances due to future policy determinants.From this research it is found that in the process of preparing corporate tax many companies do not correct fiscal financial reports, many accounts are not included in the tax calculation, so that if used can reduce the tax burden.In addition, companies can be used to gain investor trust and fairness entities.From expenditures and reports can show the fiscal can show the performance of Corporate Income Tax goes well.The second proof that in the tax preparation process using fiscal correction shows the fairness of a tax obligation.In this case the fiscal financial statements and if corrected fiscal will cause good corporate income tax performance.This shows that there are no tax arrears in a corporate entity because the company complies with company regulations.